Crop and farm level adaptation under future climate challenges: An exploratory study considering multiple objectives for Flevoland, the Netherlands. (March 2017) - Mandryk, Maryia; Reidsma, Pytrik; van Ittersum, Martin K.
Abstract: Climate change is expressed in both a shift of mean climatic conditions and an increase in the frequency and severity of weather extremes. The weather extremes are often projected to have a larger impact on agricultural production than the average increase in temperature or average change in precipitation. To cope with the impacts of future climate change, farmers will have to apply adaptation measures at crop and farm level. The choice of the adaptation measures is determined by farm resources, current layout and performance of the farm and farmers' objectives. Here we present a method to assess the importance of crop and farm level measures to adapt to climate change and extreme events considering farmers' different objectives. We used a multi-objective optimization model to generate alternative farm plans and assess the impacts of crop and farm level adaptation measures in terms of farm performance on the objectives of maximizing farm economic result (gross margin) and soil quality (soil organic matter balance); these objectives were previously identified as most important to farmers. Two local scenarios were investigated: one based on a 2 °C increase in global temperature in 2050, including changes in air circulation resulting in drier summers, and one based on a 1 °C increase in global temperature, without changes in air circulation. Our results for six surveyed arable farms in the province of Flevoland (the Netherlands) suggest that average climate change improves farm performance in terms of farm economic result. The degree of improvement varies per scenario and per farm, depending on the cropping pattern. At the same time, extreme events may reverse positive impacts of average climate change, and can pose large risks. A combination of crop and farm level adaptation is needed for the surveyed farms in terms of improving both farm economic result and organic matter balance. A shift to (more) winter wheat, in systems dominated by root crops, is an estimated effective strategy to improve the organic matter balance and maintain farm economic result under climate change and extreme events. Highlights: Method to assess adaption to climate change considering farmers' multiple objectives Extreme events reverse positive impacts of average climate change. A combination of crop and farm level adaptation is needed. Wheat area increase effective to improve SOM balance and maintain gross margin